PENGARUH MODEL QUANTUM TEACHING TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS X SMA NEGERI 10 MEDAN TAHUN PEMBELAJARAN 2012/2013 - DASMIATI DASMIATI (Basastra, 2013)
This study aimed to determine the effect on the ability of the model Quantum Teaching poetry writing class X SMA Negeri 10-year field study 2012/2013. The sample of 40 people in the experimental class and 40 in the control class, of 246 population consisting of 6 classes. Techniques used in the determination of the sample is random technique class. The sample will be divided into two classes, the experimental class and control class. The method used in this study is an experimental method to design two-group posttest study desaign. The instrument used was a test essay writing poetry. The average value of the experimental class was 77.5, while for the control class is 68.125. Based on the analysis of data obtained using the t test t count = 5.54. At the significant level α = 5%, is obtained TTable = 2.00 and the significance level α = 1%, TTable = 2.65. So, thitung> ttable = 2.00 <5.54> 2.65. Thus, Ho is rejected and Ha accepted. Based on the above data, it was concluded that the use of models of Quantum Teaching positive influence on the ability to write poetry class X SMA Negeri 10 Medan Years Learning 2012/2013. Keywords: effect, the quantum model of teaching, skills, writing, poetry